Cultural Significance of Mt. Mayon Natural Park: Albay’s Icon of Natural Heritage - Besmonte, Edgardo (Romblon State University Research Journal, 2023)
Mt. Mayon Natural Park (MMNP), commonly known as Mayon Volcano, is one of the most celebrated natural heritages in the Province of Albay. It is a classic stratovolcano that rises 2,462 m (8, 189 ft) above sea level. This paper discussed the inherent cultural significance of MMNP by utilizing the cultural mapping approach of the National Commission for Culture and the Arts (NCCA) to map significant natural resources. The informants’ articulation of the significant values of the volcano is a manifestation that the site is a significant natural property in the city. However, a lot of significant data are missing to fully provide holistic and comprehensive articulation of the significance of the volcano. From this context, this paper recommends the inclusion of MMNP in the targets for the next cultural mapping exercise of Tabaco City. Moreover, an update on the diversity and distribution assessment of flora and fauna may be considered to provide the Local Government Unit of Tabaco City with the current status of biological status of the volcano as baseline data for future efforts in the conservation and protection of the site.